The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1902/jop.2017.160767
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Stability of Root Coverage by Coronally Advanced Flap Procedures

Abstract: In this 3-year follow-up of a subgroup of patients from a previous 6-month RCT, there was a high correlation between the results for RC after 6 months and 3 years, indicating their stability. These data suggest that 6-month outcomes may be useful to predict long-term outcomes in CAF procedures with or without additional use of CMX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 29 publications
4
59
3
1
Order By: Relevance
“…Authors suggested stable clinical outcomes over the additional 6 months in terms of mean root coverage (76.3% for CAF + CMX and 75.0% for CAF) and complete root coverage (36% for CAF + CMX and 31% for CAF). Further evidence on the stability of the obtained clinical outcomes after 6‐month and 12‐month year for both procedures was further reported in a third subgroup analysis after 3‐year follow‐up (Jepsen, Stefanini, Sanz, Zucchelli, & Jepsen, ). In the present study despite greater estimates of CRC were observed, a worsening trend of the clinical results obtained was however noted between 6 and 12 months especially in the control group although this difference resulted statistically not significant.…”
Section: Discussionmentioning
confidence: 72%
“…Authors suggested stable clinical outcomes over the additional 6 months in terms of mean root coverage (76.3% for CAF + CMX and 75.0% for CAF) and complete root coverage (36% for CAF + CMX and 31% for CAF). Further evidence on the stability of the obtained clinical outcomes after 6‐month and 12‐month year for both procedures was further reported in a third subgroup analysis after 3‐year follow‐up (Jepsen, Stefanini, Sanz, Zucchelli, & Jepsen, ). In the present study despite greater estimates of CRC were observed, a worsening trend of the clinical results obtained was however noted between 6 and 12 months especially in the control group although this difference resulted statistically not significant.…”
Section: Discussionmentioning
confidence: 72%
“…For CAF + ADM, original data showed that CRC was 3/13 at 6 months and reduced to 1/13 at 2 years, and MRC was 76.18 ± 20.81% at 6 months and decreased to 68.04 ± 17.87% at 2 years (de Queiroz Cortes et al., ). In the sites treated by CAF + XCM, CRC was reported 11/18 (6 months) versus 11/18 (3 years; Jepsen et al., ) and 12/17 (6 months) versus 9/17 (5 years; McGuire & Scheyer, ). And MRC was reported 89.94 ± 14.46% (6 months) versus 91.70 ± 12.05% (3 years; Jepsen et al., ) and 89.5 ± 19.2% (6 months) versus 77.6 ± 29.2% (5 years; McGuire & Scheyer, ), respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Then, a total of 38 articles were selected for full‐text screening. Finally, 15 RCTs (Abolfazli, Saleh‐Saber, Eskandari, & Lafzi, ; Amarante, Leknes, Skavland, & Lie, ; Bittencourt et al., ; Cortellini et al., ; Del Pizzo, Zucchelli, Modica, Villa, & Debernardi, ; Fernandes‐Dias et al., ; Jepsen et al., , ; Kuis et al., ; Leknes et al., ; McGuire & Nunn, ; McGuire & Scheyer, , ; McGuire, Scheyer, & Nunn, ; McGuire, Scheyer, & Schupbach, ; McGuire, Scheyer, & Snyder, ; Nizam, Bengisu, & Sonmez, ; Pini Prato et al., ; Pini‐Prato et al., ; de Queiroz Cortes, Sallum, Casati, Nociti, & Sallum, ; Rasperini et al., ; Rosetti, Marcantonio, Zuza, & Marcantonio, ; Santamaria et al., ) fulfilled the inclusion criteria. The rest 23 studies were excluded for different reasons (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations